Nelson Mandela : South Africa's anti-apartheid revolutionary - Dakers, Diane (Crabtree Pub. Co., 2014)
Chronicles the life and accomplishments of Nelson Mandela, a South African political activist who was imprisoned for his rebellion against racial segregation and was later elected as the first black president of South Africa.